PENGGUNAAN MEDIA LINGKUNGAN PADA PEMBELAJARAN BIOLOGI DI KELAS X MAN 4 PIDIE - Erlinawati (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2018)
This study aims to improve the learning outcomes of Biology students of 10th grade MAN 4 Pidie through the use of environmental media as a learning resource. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles. Data collection techniques are carried out through tests, observation sheets, and documentation. The subjects of this study are 36 students of 10th grade of MAN 4 Pidie. The results of the study in cycle I were 65.25% and in cycle II it became 91.5% or an increase of 26.25%. So it can be concluded that the use of environmental media can improve biology learning outcomes.